Use of Microsoft Forms to Practice Reading Comprehension of German Short Text for 12th Grade Students at SMAN 9 Malang - Sari, Dhiyah Kumala; Retnantiti, Sawitri (Universitas Negeri Malang, 2024)
The research was conducted with the aim of describing how to use Microsoft Forms for practicing reading comprehension german short text and describing the response of 12th Grade IPS 3 Students at SMAN 9 Malang towards the implementation of them. Microsoft Form is an online application which can be use for creating quiz In a simple and easy way especially for practice questionsshort text comprehension. Collected data is result of observation sheets and student questionnaire sheets which were analyzed using qualitative descriptive methods. The results are: the use of Microsoft forms runs well and smoothly according in the RPP. This App help students comprehend short texts true or false, multiple choice, practice questions and can make good questions and statements. Immersive audio reader makes it easy for students to pronounce German and other students can correct their friend’s pronunciation errors. Learning using Microsoft form get positive response from students and this Apps help them comprehend German short texts and their pronunciations.